2021
DOI: 10.1155/2021/6660486
|View full text |Cite
|
Sign up to set email alerts
|

Id4 Suppresses the Growth and Invasion of Colorectal Cancer HCT116 Cells through CK18-Related Inhibition of AKT and EMT Signaling

Abstract: Id4 is one of the inhibitors of DNA-binding proteins (Id) and involved in the pathogenesis of numerous cancers. The specific mechanism underlying the Id4-mediated regulation of proliferation, invasion, and metastasis of colorectal cancer (CRC) cells is still largely unclear. In the present study, results showed CRC cells had a lower baseline Id4 expression than normal intestinal epithelial NCM460 cells. In order to explore the role of Id4 in the tumorigenicity, CRC HCT116 cells with stable Id4 expression were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Previous research has reported that ID4 acts as a tumor suppressor in CRC progression [ 21 , 22 ]. We conducted the rescue experiments to confirm the interaction between circTMEM59 and ID4 of CRC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has reported that ID4 acts as a tumor suppressor in CRC progression [ 21 , 22 ]. We conducted the rescue experiments to confirm the interaction between circTMEM59 and ID4 of CRC.…”
Section: Resultsmentioning
confidence: 99%
“…ID4 was identified as a target of miR-668-3p through luciferase reporter and RIP assays, which was abnormal in different types of cancer [ 37 39 ]. Importantly, ID4 is reportedly an inhibitor of CRC progression [ 21 , 22 ]. As expected, ID4 was simultaneously decreased in CRC tissues and larger tissues compared with that in adjacent tissues and smaller tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, due to differences in regulatory mechanisms, a gene can have different functions in the same organ carcinomas. In colorectal cancer, inhibitors of DNA-binding protein 4 (ID4) can promote tumorigenesis by targeting brain-derived neurotrophic factor (BDNF) (37), and can also inhibit tumor growth and metastasis by inhibiting PI3K/AKT pathway and inhibiting epithelial-mesenchymal transition (EMT) in a CK18-Related manner (38). Therefore, the hsa_circ_0001675/miR577/TESC pathway in HNC needs to be experimentally verified, and the specific mechanism of TESC needs further study.…”
Section: Discussionmentioning
confidence: 99%
“…Id4 inactivated AKT and PI3K, suppressing CRC cell proliferation through modulating PI3K/AKT signaling. Id4 mitigated the EMT process as it up regulated TIMP1/2 and down regulated the snail, slug, twist, β-catenin, MMP2, and MMP7 [ 51 ]. GATA1 is a critical modulator of erythroid cell apoptosis, proliferation, and differentiation.…”
Section: Transcription Factors and Chromatin Remodelersmentioning
confidence: 99%